Survival Analysis in Stroke Patients with Cerebral Small Vessel Disease - Bartiuk , R.S.; Smolko , D.G.; Marunkevych , Ya.Yu.; Smotrytska, T.V.; Moskovko, S.P. (Medicni Perspektivi, 2025)
Cerebral small vessel disease has been considered to worsen short-term stroke outcome in upcoming 90 days, whereas few research have evaluated the role of cerebral small vessel disease in long-term prognosis (for instance, beyond a year). The aim of the research is to investigate the association between cerebral small vessel disease burden and long-term post-stroke survival in patients with acute stroke. It was a prospective single-center cohort study. 294 consecutive patients with acute stroke were recruited. All participants underwent magnetic resonance imaging and computed tomography assessment for cerebral small vessel disease markers as well as clinical-neurological testing.. To determine the associations of small vessel disease with mortality in patients after stroke, we used multivariate survival analysis using Cox regression with Kaplan-Meier survival curves for 5 years of follow-up after discharge. In multivariable Cox regression proportional hazards model, cerebral small vessel disease presence was associated with long-term all-cause post-stroke mortality (hazard ratio =3.8; 95% confidence interval 1.9-7.9, p<0.001). In the same model, cerebral small vessel disease severity grade 1 (hazard ratio =2.4; 95% confidence interval 1.1-5.4, p=0.033), cerebral small vessel disease severity grade 2 (hazard ratio =6.9; 95% confidence interval 3.2-15.0, p<0.001) were associated with poor survival. We also found significant association between presence of lacunes and mortality: (adjusted hazard ratio =6.2; 95% confidence interval 3.3-11.5, p<0.001); as well as severe white matter hyperintensity and mortality: (adjusted hazard ratio =2.1; 95% confidence interval 1.1-4.1, p=0.019). Cerebral vessel disease is significantly associated with mortality in patients after stroke during 5 years of follow-up. It may be useful in determining patient prognosis and future patient selection for preventive strategies.